Bahasa Inggris - Angela, Ika (Universitas Multimedia Nusantara, 2024)
In Chinese-Asian culture, sons are often viewed as symbols of luck and hope, which leads parents to invest heavily in their futures. However, when a son is married, this deep connection can lead to tension, especially between his mother and wife. The son then finds himself in the tricky position of balancing both relationships between the Mother-in-Law (MIL) and the Daughter-in-Law (DIL). Lahn Mah (Pat Boonnitipat, 2024) known in English as How to Make Millions Before Grandma Dies, captures this dynamic with several scenes exploring the relationships among son, MIL, and DIL. Therefore, this study examines visual signs that convey the distance in the relationships between sons, MIL, and DIL in Lahn Mah. This research employs a descriptive qualitative methodology with Ferdinand de Saussure's semiotic analysis approach. The findings reveal nine key scenes illustrating varying distances between the son, MIL, and DIL. These distances shift as the story unfolds: wide gaps signify conflict, while closeness indicates reconciliation. Keywords: distance; sons; in-laws; film; semiotic